PENDAMPINGAN SAINS TERAPAN UNTUK MENINGKATKAN KOMPETENSI GURU-GURU IPA DALAM PEMBELAJARAN PRAKARYA DI KABUPATEN SIJUNJUNG - Renol Afrizon; Hidayati Hidayati; Relsas Yogica (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2020)
Mentoring Activities of Applied Science to Improve the Competence of Natural Science Teachers in Prakarya Learning in Sijunjung RegencyAbstract. Junior high school natural science teachers in Sijunjung Regency are still not optimal in teaching of prakarya. This is due to the lack of application of natural science in prakarya learning. Prakarya subjects have four material aspects, namely: crafts, engineering, cultivation, and processing. The material aspect of crafts is more dominantly taught by science teachers in prakarya subjects even though this material aspect is more appropriate to be taught by arts / culture teachers. In addition, there are still very few natural science teachers who are able to compile prakarya student worksheets. The Community Partnership Program in the form of mentoring activities of applied natural science is very much needed by natural science teachers in learning prakarya. This activity aims to motivate and help natural science teachers to continue to improve their competencies, especially professional and pedagogical competencies. Community service activities in the form of mentoring activities use a method that consists of several stages. The initial stage is the orientation and discussion phase. The second stage is the preparation phase of the activity. The third stage is the mentoring stage 1 (in) with use the explanation, demonstration, and practice methods on mentoring activity. Data collection techniques with pre-test and post-test methods and analyzed using normalized gain. This activity has been carried out for 5 months from March to July 2019 at SMP Negeri 11 Sijunjung, Kamang Baru District, Sijunjung Regency, West Sumatra Province. The results of the activities showed that increasing the pedagogical competence of the Sijunjung district's natural science teachers in the prakarya learning was satisfactory. Meanwhile, increasing professional competence is quite satisfying. So, overall the improvement in the competence of Sijunjung district's natural science teachers in prakarya learning has been satisfactory.Keywords: Community service, applied natural science, prakarya, professional, pedagogicalAbstrak. Guru-guru IPA SMP di Kabupaten Sijunjung masih belum optimal dalam mengajarkan prakarya. Hal ini disebabkan karena masih kurangnya penerapan IPA dalam pembelajaran prakarya. Mata pelajaran prakarya memiliki empat aspek materi yaitu: kerajinan, rekayasa, budidaya, dan pengolahan. Aspek materi kerajinan lebih dominan diajarkan oleh guru IPA dalam mata pelajaran prakarya padahal aspek materi ini lebih tepat diajarkan oleh  guru seni budaya/keterampilan. Selain itu, masih sedikitnya guru IPA yang mampu menyusun bahan ajar prakarya. Program Kemitraan Masyarakat dalam bentuk pendampingan implementasi sains terapan sangat diperlukan guru IPA dalam pembelajaran prakarya. Kegiatan ini bertujuan untuk memotivasi dan membantu guru-guru IPA untuk terus meningkatkan kompetensinya terutama kompetensi professional dan pedagogik. Kegiatan pengabdian masyarakat dalam bentuk kegiatan pendampingan ini menggunakan metode yang terdiri dari beberapa tahapan. Tahap awal yang dilaksanakan adalah tahap orientasi dan diskusi. Tahap kedua berupa tahap persiapan kegiatan. Tahap ketiga adalah tahap pendampingan 1 (in) dengan menggunakan metode ceramah, demonstrasi, dan praktik pada kegiatan pendampingan. Teknik pengumpulan data dengan metode pre-test dan post-test dan dianalisis menggunakan gain ternormalisasi. Kegiatan ini telah dilaksanakan selama 5 bulan dari bulan Maret sampai dengan Juli 2019 di SMP Negeri 11 Sijunjung Kecamatan Kamang Baru, Kabupaten Sijunjung Provinsi Sumatera Barat. Hasil kegiatan menunjukkan bahwa peningkatan kompetensi pedagogik guru-guru IPA kabupaten Sijunjung dalam pembelajaran prakarya sudah memuaskan. Sedangkan, peningkatan kompetensi profesionalnya cukup memuaskan. Jadi, secara keseluruhan peningkatan kompetensi guru-guru IPA kabupaten Sijunjung dalam pembelajaran prakarya sudah memuaskan.Kata Kunci: Pengabdian, sains terapan, prakarya, profesional, pedagogik